Mexican Costumbrismo : Race, Society, and Identity in Nineteenth-Century Art - Moriuchi, Mey-Yen, 1974- (Book collections on Project MUSE., 2018)
"Focuses on costumbrismo, a cultural trend in Latin America and Spain toward representing local customs, types, and scenes of everyday life in the visual arts and literature, to examine the shifting terms of Mexican identity in the nineteenth century"--